Penampilan Reproduksi Sapi Bali pada Peternakan Intensif di Instalasi Pembibitan Pulukan - Mahmud Siswanto; Ni Wayan Patmawati; Ni Nyoman Trinayani; I Nengah Wandia; I Ketut Puja (Veterinary Science and Medicine Journal, 2013)
This studi was conducted to investigate the reproductive performances  of Bali cattle under intensive management in breeding instalation Pulukan Bali from  2008  to  2010.  Totaling 298 2 - 6.5 year old heifers were use to represents the benchmark reproductive performances of Bali cattle. Data collected were age at first heat (AFH), age at first calving (AFC), calving interval (CI), and services per conception (SPC). The overall means for  AFH, AFC,and  CI  were  718.57 ± 12.65; 1104.51 ±  23.82, and 350.46 ± 27.98 days  respectively,  and SPC was 1.65 ± 0.87.